2019
DOI: 10.1002/cam4.2654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serum from breast cancer surgery patients receiving perioperative dexmedetomidine on breast cancer cell malignancy: A prospective randomized controlled trial

Abstract: Adrenergic receptors (ARs) have gained attention for their involvement in breast cancer (BC) progression. Dexmedetomidine, a selective α2‐AR agonist, has been reported to increase the malignancy of BC cells in vitro or stimulate tumor growth in mice. However, clinical evidence is lacking. Clinical research in this area is important as dexmedetomidine is widely used in BC surgery patients. Here we allocated 24 women with primary BC to the dexmedetomidine group (who received a total dose of 2 μg kg−1 dexmedetomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Wang et al (49) demonstrated that Dex could promote tumor cell migration by activating the a2-AR/ STAT3 pathway and the secretion of the exosomal protein TMPRSS2 in breast cancer. We also previously found that postoperative serum from patients administered with Dex during surgery promoted BC cell proliferation, migration, and invasion, indicating that Dex worsens the prognosis of patients BC (50). Additionally, there is a paucity of studies on the prognostic effects of muscle relaxants, a blocker of the binding between Ach and nAchRs, in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (49) demonstrated that Dex could promote tumor cell migration by activating the a2-AR/ STAT3 pathway and the secretion of the exosomal protein TMPRSS2 in breast cancer. We also previously found that postoperative serum from patients administered with Dex during surgery promoted BC cell proliferation, migration, and invasion, indicating that Dex worsens the prognosis of patients BC (50). Additionally, there is a paucity of studies on the prognostic effects of muscle relaxants, a blocker of the binding between Ach and nAchRs, in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the effects of dexmedetomidine on tumor cells are as follows: it directly activates tumor alpha-2 adrenoreceptors [ 12 , 18 ], affects the capillary diameter or permeability of tumor cells [ 10 ], and drives microstructural changes in the tumor environment, causing proliferation, local invasion, and metastasis of tumor cells [ 11 ]. Additionally, current clinical evidence has raised concerns regarding the perioperative use of dexmedetomidine in patients with several types of cancer [ 14 , 15 , 16 , 17 , 18 ]. In breast cancer, dexmedetomidine has promoted cancer progression in vivo and in vitro by acting on alpha-2 adrenoreceptor and activating extracellular signal-related protein kinases [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent in vivo study has shown that dexmedetomidine inhibits esophageal cancer progression via miR-143-3P/epidermal growth factor receptor pathway substrate 8 [ 7 ]. However, results of in vitro and in vivo studies of dexmedetomidine revealed that tumor cell proliferation and metastasis are promoted, and overall survival is reduced [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In contrast, Owuso et al reported that dexmedetomidine did not affect the survival of patients who underwent cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for peritoneal carcinomatosis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this effect, a prospective randomized controlled trial that exposed the postoperative serum of breast cancer patients who received dexmedetomidine to MCF-7 cells observed significantly elevated MCF-7 cell proliferation, migration, and invasion compared with preoperative serum. 144 This indicates that in patients undergoing primary breast cancer surgery, perioperative use of dexmedetomidine may influence the serum milieu in a way that encourages the malignancy of breast cancer cells.…”
Section: Key Surgical Applicationsmentioning
confidence: 99%